Impact of incarceration on rates of methadone use in a community recruited cohort of injection drug users. (July 2015) - Koehn, John D.; Bach, Paxton; Hayashi, Kanna; Nguyen, Paul; Kerr, Thomas; Milloy, M.-J.; Rieb, Launette; Wood, Evan
Abstract: Background: Despite barriers to its use in many settings, opioid agonist therapy with methadone has become the standard of care for treating opioid (e.g. heroin) use disorder. Since people with opioid use disorders have an increased incidence of incarceration, we undertook the present study to evaluate the association between incarceration and methadone maintenance therapy among a cohort of injection drug users in a Canadian setting. Methods: A cohort of people who inject drugs was prospectively followed between May 1996 and May 2013 in Vancouver, Canada. We investigated the relationship between recent incarceration and methadone use using multivariate generalized estimating equation (GEE) logistic regression analysis. Results: Overall, 2758 individuals were recruited during the study period and followed for a median of 64 (interquartile range: 23–106) months. After adjusting for various potential confounders in the multivariate GEE model, being incarcerated remained independently associated with a lower likelihood of having received methadone treatment (Adjusted Odds Ratio: 0.87, 95% confidence interval: 0.81–0.93). Conclusions: Our study demonstrates that incarceration was independently associated with a significantly lower likelihood of being on methadone. Given the role of methadone in reducing the harms of heroin use, including drug acquisitive crime and recidivism, these data suggest a need to scaleup methadone provision for incarcerated injection drug users. Highlights: Opioid addiction is associated with incarceration and severe health consequences. Methadone maintenance therapy is the standard of care for opioid addiction. Recent incarceration decreases the likelihood of being on methadone.